Pengelolaan Keuangan Badan Layanan Umum Daerah (BLUD) dan Pengaruhnya Terhadap Kinerja Rumah Sakit (Studi Kasus pada RSUD Nganjuk) - Dian Candra Oktavia; Maslichah Maslichah; Abdul Wahid Mahsuni (Universitas Islam Malang, 2023)
This research was conducted to determine the pattern of financial management of the Regional Public Service Agency (BLUD) at Nganjuk Regional Hospital and its effect on hospital performance both in terms of financial performance and service performance. This research uses qualitative methods.Nganjuk Regional General Hospital implements the Regional Public Service Agency (PPK-BLUD) Financial Management Pattern with full status. In general, the condition of the Nganjuk Regional General Hospital is stable enough to make changes in an effort to improve the hospital's performance. Based on the results of this study, which is reviewed from financial performance, it shows that the financial performance of Nganjuk Hospital in the 2019-2021 period received BB (moderate) criteria with an achievement value of 47.63% while in the service performance of Nganjuk Hospital. Meanwhile, in terms of service performance at Nganjuk Regional Hospital in 2019-2021, there are still several indicators that have not been achieved against the target that has been set due to hospital visits decreasing during the pandemic.Keywords : PPK-BLUD, Financial performance, service performance